Perjuangan Tokoh Utama dalam Novel Laut Bercerita Karya Leila S Chudori - Rita Fitriana; Emi Agustina; Bustanuddin Lubis (UNIB Press, 2026)
The purpose of this study is to describe the social problems and values of struggle contained in the novel Laut Bercerita. The method used is descriptive qualitative. This research examines the novel Laut Bercerita using a literary sociology approach in terms of the content of literary works. The data source in this research is a novel entitled Laut Bercerita by Leila S Chudori. The data in this study are in the form of quotations of social problems and the values of the struggle of the main character in the novel Laut Bercerita. The data collection technique uses literature study. Data analysis techniques by reading and understanding, making a synopsis, marking and recording, analyzing, and making conclusions. The main characters in this novel, Biru Laut and Asmara Jati, are often discussed and prioritized. The results show that the social problems contained in the novel Laut Bercerita are about the problem of arbitrariness, and acts of violence. These social problems have an impact related to the values of struggle. The values of the struggle of the main character in the novel Laut Bercerita, among others; the value of self-sacrifice, the value of enthusiasm and never giving up, the value of cooperation, the value of respect and the value of patience. These values are the drivers and reinforcers of the struggle.